PELATIHAN BERBALAS PANTUN SISWA KELAS XII SMA NEGERI 2 SIAK HULU KABUPATEN KAMPAR - Shomary, Sudirman; Kalsum, Umi; Yuliawan, Tri; Sudirman, Nurul Aini (Komunitas Manajemen Kompetitif, 2023)
Learning to read or reply to rhymes is very important for high school students. Apart from practicing literary skills, reading rhymes can also train students' mental abilities to perform in front of many people. Apart from that, reading rhymes can also build students' character and personality because rhymes contain many messages and moral values. Difficulty reading rhymes often occurs in high school environments. Many teachers complain when their students are reluctant to respond to rhymes. This happens because students have not had the experience of learning to read rhymes correctly. This kind of learning needs to be improved, so it is necessary to hold rhyme reading training for high school students which can be done by practicing correct pronunciation, tone, stress, intonation, appreciation and expression. The problem with this activity is how to improve the knowledge and skills of responding to rhymes in Class XII students at SMA Negeri 2 Siak Hulu, Kampar Regency? The aim of this community service activity is to provide knowledge and practice of reading or responding to rhymes appropriately according to good and correct techniques. The community service method uses lecture and experimental methods. The resource person explains the theory about rhymes and how to read or reply to rhymes well. The rhyme used is the opening the door rhyme or escorting the bride and groom. Based on the success criteria, students of SMA Negeri 2 Siak Hulu, Kampar Regency were able to respond to rhymes after the training was completed. This was shown by the students' enthusiasm when the community service team asked them to read a poem again in front of the class. They have been able to pronounce, give intonation, chop up words, and express them correctly. Thus, this training activity can be said to have been successful. After the training was carried out, participants were given a partner satisfaction questionnaire regarding PKM activities for Class XII Students of SMA Negeri 2 Siak Hulu, Kampar Regency. The questionnaire was used to determine participants' knowledge after the training was given.